Adverse childhood experiences, sentinel injuries, and effective clinical responses: Can we do better? – A Canadian perspective - Megan Cooney; Suzanne Kathleen Robinson (Child Protection and Practice)
Medically minor abusive injuries, known as sentinel injuries, are often missed in clinical settings. Child physical abuse, which frequently presents with medically minor or no visible injury, is a common adverse childhood experience (ACE). Practitioners are not typically trained to consider the increased risk of detrimental outcomes described with ACE exposures when young children present with sentinel injuries. However, these injuries may be the only visible signs that a young child is at increased risk of detrimental health, social, and behavioral concerns both imminently and over the lifespan. This Practice Perspective aims to describe common sentinel injuries, discuss why they are underrecognized by practitioners, and describe the clinical approach to assessing these injuries from a Canadian perspective. It will also discuss how improving recognition could decrease subsequent severe presentations with child maltreatment while also identifying children at risk for the detrimental outcomes described in adults with exposures to ACEs.